PENANGGULANGAN PRAKTIK ILLEGAL FISHING DI ZONA EKONOMI EKSKLUSIF INDONESIA - Bagus Agastya, Made; Parwata, I Gusti Ngurah (Kertha Desa, 2022)
The purpose of this paper is to identify and analyze the modus operandi of illegal fishing practices and efforts to combat illegal fishing practices in the Indonesian Exclusive Economic Zone. Writing scientific papers uses normative research. This paper uses a statute approach and a conceptual approach. The technique of tracing legal materials uses document study techniques and the analysis of studies uses qualitative analysis. The study results show that the modus operandi used in illegal fishing practices in Indonesia's EEZ includes fishing without a permit, fishing using fake permits, fishing using illegal fishing gear and catching fish with types or species that are not in accordance with the permit. Indonesia as a coastal country can carry out efforts to combat illegal fishing practices through authorized law enforcement officials in accordance with the provisions of laws and regulations.